The use of genre analysis in the design of electronic meeting systems - Antunes, P. (2018)
Introduction. Genre analysis is an approach to study communication patterns and thus it can be applied to the specific context of meetings. This research investigates the use of genre analysis in the design of electronic meeting systems. Background. The primary goal of genre analysis is to understand how virtual communities use digital communication to collaborate. This knowledge is fundamental for informing the design of information systems, particularly in areas where communication and informality are paramount. However, the research literature does not report any experiments where genre analysis has been used to inform the design of electronic meeting systems. Problems. The paper tackles the following common problems found in current electronic meeting systems: (1) reduced organizational integration, neglecting many contextual cues and explaining factors necessary to make meeting outcomes usable within the organization; (2) lack of support to specific communities of users, stressing the dependency on a facilitator to configure and manage the technology; and (3) lack of support to meeting occurrences that span long time periods. Conclusions. The paper describes how genre analysis was used to develop electronic meeting systems for several organizations and meeting genres. It covers the complete design process, from genre elicitation to validation. The obtained results demonstrate that the genre approach produces electronic meeting systems focused on organizational integration, pre-configured to communities of users, supporting long-term usage and added organizational value.